Treatise on thermodynamics - Planck, Max, 1858-1947 (Dover, 1990)
This classic by the Nobel Laureate is still recognized as one of the best introductions to thermodynamics. A model of conciseness and clarity, it covers fundamental facts and definitions, first and second fundamental principles of thermodynamics, applications to special states of equilibrium, and much more. Numerous worked examples. 1917 edition.